Hypnosis Breastfeeding (Hypnobreastfeeding) to Improve Breastfeeding Self Efficacy in Postpatum Mother at Kediri City - Rohmah, Miftakhur; Wahyuni, Candra; Mufida, Riza Tsalatsatul (Jurnal MIDPRO, 2021)
The benefits of breastfeeding for the health of mothers and children have been substantially proven. However, exclusive breastfeeding for 6 months in Indonesia is still low in achievement, this is associated with low self-efficacy in breastfeeding. The purpose of this study was to determine the effect of hypnobreastfeeding on breastfeeding self-efficacy for postpartum mothers in Kediri City in 2021.The research design used was a quasy experiment with a nonequivalent control group design approach. Involving 40 postpartum mothers as respondents consisting of 20 treatment groups and 20 control groups, which were taken by purposive sampling. The statistical test used in this study is the Mann Whitney test.The results showed that the rest-feeding self-efficacy in the control group was mostly in the category of less than 80% (16 people), and in the treatment group mostly in the good category of 85% (17 people). The results of statistical tests using Mann Whitney obtained p-value (0.00 <0.05), which means that there is an effect of giving breastfeeding hypnosis (hypnobreastfeeding) on breastfeeding self-efficacy in postpartum mothers. Planting positive affirmations through hypnobreastfeeding into one's subconscious mind, can increase the mother's confidence in breastfeeding so that breastfeeding can be optimal for babies and achieve exclusive breastfeeding.